DEPLOYMENT OF 5S SYSTEM IN ARCHIVES MANAGEMENT - Cavaglieri, Marcelo; Juliani, Jordan Paulesky (Informação em Pauta, 2017)
An efficient document management brings various benefits, not only for professionals of the area but, mainly, for business managers who can use this information in their decisionmaking to enjoy competitive advantages on competitors. Having in mind that effectiveness is a constant pursuit for any company in order to achieve their strategic goals and improve the techniques which enable more productivity using fewer financial resources. In this sense, it was sought to apply the 5S philosophy in the document file management of Santa Fé Company, once it is necessary to improve the current processes with less waste and more efficiency, with a view to the need to suit the client more efficiently before their information necessities. Regarding to the method used, it is characterized as a researchaction in a quali-quantitative approach, classified as exploratory and descriptive. Among the obtained research results, it stands out in a quantitative way the reduction of waste, with significant gains of Lead Time, diminishing the time to process the activities. Financial gains were also obtained with a better use of resources and a redesigning of the way to keeping the documents. In a qualitative way, a better working environment is highlighted and increase of the service efficiency in bringing more customer satisfaction.